محاور التجديد النحويّ عند ابن مضاء القرطبيّ (من خلال كتابه الرد على النحاة) - بابكر, محمد الطيّب البشير (Journal of Faculty of Education, 2022)
تناولتْ هذه الدراسة المحاور التي استند عليها ابن مضاء القرطبيّ في ثورته التي هدف من خلالها إلى التجديد في النحو العربيّ ، وذلك من خلال كتابه(كتاب الرد على النحاة). وقد هدفتْ الدراسةُ إلى حصر تلك المحاور ومناقشة محورين فقط منها ، كما هدفتْ الدراسةُ ــــ كذلك ــــ إلى بيان مدى أثر تلك المحاور على النحو العربيّ . واتَّبعت الدراسةُ في ذلك المنهجَ الوصفي ، الذي يقوم على جمع المادة وتصنيفها وتحليلها بغية الوصول إلى تحقيق أهداف الورقة المنشودة. وتوصلتْ الدراسةُ بعد إلى جملة من النتائج ولعلَّ من أهمها : كتاب الرد على النحاة من أوائل الكتب النحويَّة التي صرَّحت بالدعوة للتجديد في النحو العربي.نظرية العامل في النحو العربي هي عمود النحو وقطب رحاه ، وهدمها يعني هدماً للنحو العربيّ جملة وتفصيلاً . العلل الثواني والثوالث لا تفيد الدارسين في معرفة الأحكام النحوية ، وإنَّما تمكِّن فقط من التعرف على الحكمة العميقة من نسج كلام العرب على هذا النمط . أصاب ابن مضاء في آرائه المتعلقة بالعلل والتعليل بينما لم يحالفه الصواب في دعوته إلى إلغاء نظرية العامل . وأوصتْ الدراسة في خاتمتهاباستكمال البحث في تلك المحاور التي لم تتطرق إليها هذه الورقة. This study dealt with the domains upon which IbnMudaaAlqurtobei has depended in his revolution in which he aims at renewal of Arabic syntax, that was in his book (the book of answering the grammarians). The study aimed at counting those domains and discussing two of them. The study also aimed at explaining the extent of those domains on Arabic syntax. The study used the descriptive approach that depends on collection of e data, classifying, and analyzing it so as to come to the desired objectives of the study. Most important findings are: the book named (answering the grammarians )is considered one of the first books that declared calling for renewing Arabic syntax. The theory of word governing another is the backbone and focus of syntax, its destruction means the destruction of the language all together. The second and the third word governing another are not useful for researchers in knowing syntax rules, but they enable identifying the deep reason behind cancellation of Arab speech that way. IbnMudaa was right in his opinions concerning causes and justification, but he was unsuccessful in his calling for cancelling the theory of word governing another. In its end, the study recommended addressing research in those domains which the paper did not mention.